2015
DOI: 10.1111/bcp.12536
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid insensitive alveolar macrophages from asthma patients; synergistic interaction with a p38 mitogen‐activated protein kinase (MAPK) inhibitor

Abstract: Aims Some asthma patients remain symptomatic despite using high doses of inhaled corticosteroids (ICS). We used alveolar macrophages to identify individual patients with insensitivity to corticosteroids and to evaluate the anti‐inflammatory effects of a p38 mitogen‐activated protein kinase (MAPK) inhibitor combined with a corticosteroid on these cells. Methods Alveolar macrophages from 27 asthma patients (classified according to the Global Initiative for Asthma (GINA) treatment stage. Six GINA1, 10 GINA2 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Ratcliffe and Dougall reported similar findings with COPD lung macrophages; there was a subset of patients with a reduced response to corticosteroids [ 28 ]. Similarly, corticosteroids have heterogeneous effects on alveolar macrophage cytokine production in patients with asthma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ratcliffe and Dougall reported similar findings with COPD lung macrophages; there was a subset of patients with a reduced response to corticosteroids [ 28 ]. Similarly, corticosteroids have heterogeneous effects on alveolar macrophage cytokine production in patients with asthma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination studies with dexamethasone showed synergistic anti-inflammatory effects on cytokine production in poly I:C-stimulated epithelial cells. Birb796 has anti-inflammatory synergistic effects with dexamethasone in LPS-stimulated COPD macrophages [7], and p38 MAPK inhibition can reverse corticosteroid insensitivity in cellular models and cells from asthma patients [22][23][24]. P38 MAPK phosphorylates the glucocorticoid receptor (GR) [25].…”
Section: Cellular Modelsmentioning
confidence: 99%
“…Despite the demonstrable benefit of inhaled glucocorticoids (GCs) for improving asthma symptoms and lung function in patients with asthma, referred to as steroid-sensitive (SS) asthma, it is estimated that ≤5% of asthma cases are relatively insensitive to steroid therapy (1). Aside from Th17-induced airway inflammation, it is apparent that activation of monocytes and macrophages is associated with steroid-resistant (SR) asthma (2,3). Macrophage-induced airway inflammation in mice is associated with SR airway inflammation and airway hyperresponsiveness (AHR) (4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that p38 MAPK pathway activation in peripheral blood mononuclear cells (PBMCs) is significantly increased in patients with SR asthma compared with patients with SS asthma (8). In addition, previous studies showed that inhibition of p38 MAPK pathway activation using vitamin D or p-p38 MAPK inhibitor significantly enhanced dexamethasone (DEX)-induced inhibition of cellular responsiveness to GCs in patients with SR asthma (3,12,13). Therefore, targeting the GRE-based signaling pathway may be a novel therapeutic strategy for SR asthma.…”
Section: Introductionmentioning
confidence: 99%